Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s00018-005-4531-7
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C and phospholipase D: intimate interactions in intracellular signaling

Abstract: Diacylglycerol (DAG) was discovered as a potent lipid second messenger with protein kinase C (PKC) as its major cellular target more than 25 years ago. There is increasing evidence of significant complexity within lipid signaling, and the classical DAG-PKC model no longer stands alone but is part of a larger bioactive lipid universe involving glycerolipids and sphingolipids. Multiple layers of regulation exist among PKC- and DAG-metabolizing enzymes such as phosphatidylcholine (PC)-specific phospholipase D, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 122 publications
2
49
0
1
Order By: Relevance
“…Moreover, DAG produced by complex sphingolipid metabolism has been shown to activate PKC in the pathogenic fungi Cryptococcus neoformans (74). Conversely, ceramides, which are immediate precursors and turnover products of complex sphingolipid metabolism, inhibit PKC activation in mammals (75,76). However, because DAG levels are expected to decrease and ceramide levels are expected to increase when complex sphingolipid synthesis is inhibited during inositol starvation, neither DAG nor ceramides are likely to significantly contribute to PKC activity under this growth condition.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, DAG produced by complex sphingolipid metabolism has been shown to activate PKC in the pathogenic fungi Cryptococcus neoformans (74). Conversely, ceramides, which are immediate precursors and turnover products of complex sphingolipid metabolism, inhibit PKC activation in mammals (75,76). However, because DAG levels are expected to decrease and ceramide levels are expected to increase when complex sphingolipid synthesis is inhibited during inositol starvation, neither DAG nor ceramides are likely to significantly contribute to PKC activity under this growth condition.…”
Section: Discussionmentioning
confidence: 99%
“…The generation of lipid second messengers has long been recognized to be important in the effector function of mast cells as well as in other cell types (Becker and Hannun, 2005;Rivera and Olivera, 2007;Spiegel, Foster and Kolesnick, 1996). The recent advances have clearly demonstrated that lipid messengers can be dominant in certain signaling pathways and cause cellular responses independent of many of the additional events initiated by FcεRI activation.…”
Section: B Marrying Of Lipids In the Regulation Of Calcium And Mast mentioning
confidence: 99%
“…However, phospholipase C activity should also produce IP-3 that releases calcium from internal stores, and 5-HT does not increase resting calcium levels in sensory neurons, whereas injected IP 3 does (Blumenfeld et al, 1990). Alternatively, it is possible that 5-HT activates phospholipase D, producing phosphatidic acid, which is then converted to DAG (Becker and Hannun, 2005); in this case, IP 3 is not produced. The failure of Apl II to translocate in motor neurons is most simply explained by the lack of a 5-HT GPCR coupled to DAG production.…”
Section: Translocation Of Apl II By 5-ht Alonementioning
confidence: 99%